Determinants of the demographic impact of HIV-1 in sub-Saharan Africa: the effect of a shorter mean adult incubation period on trends in orphanhood. - Gregson,S; Garnett,GP; Shakespeare,R; Foster,G; Anderson,RM (Health Transit Rev, 1994)
Recent evidence suggests that the adult HIV-1 incubation period may be shorter in some sub-Saharan African populations than in Western populations. In this article we use mathematical-model-based simulations to show that, other things being equal, a shorter incubation period can result in smaller but more pronounced HIV-1 epidemics and faster, more acute, changes in demographic features, such as adult mortality, orphanhood and population structure. Empirical studies of orphanhood reveal similar patterns to those found in the simulations, but suggest that migration patterns and structural factors can give rise to greater concentrations of orphans in areas of relatively low HIV-1 prevalence.